ANALISA KEANDALAN TERHADAP LIFETIME SYSTEM PENDINGIN KAPAL IKAN KM. RUKUN ARTA SENTOSA 06 MENGGUNAKAN REFRIGERAN CO2 DAN KOMPRESI BANTU DARI ENERGI PANAS - Hadi, Eko Sasmito; Manik, Parlindungan (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2008)
The cooling system using CO2 refrigerant is one of the vital systems to increase the quality of hauled fishing and it is more effective and more efficient and also this system is environmentally harmless than the conventional cooling system. Reliability is one of so many criteria that had to be concerned in the process of taking the decision of invention such as planning/drafting, production, or reparation process. The aim of this research is to evaluate the design of fish hatch cooling system using CO2 refrigerant and auxiliary compression by heat power in KM. RAS (Rukun Arta Sentosa) 06 using the approximation based on reliability. Some steps that had been used in this research are collecting the data, design process, and evaluation by qualitative and quantitative approach. The qualitative approach is using the Failure Mode and Effect Analysis (FMEA) method and also using Fault Tree Analysis (FTA) method. Otherwise, the quantitative approach is using the method of Markov Process. Analytical approach is done by make a design model of the available invention system through the block diagram reliability and decrease the reliability function of the system, and for the next step those system is to be used as the base rule of quantitative evaluation system. The report of the research tells that the severity level and the failure rate are showed in some components, such as compressor, condenser, heat exchanger and expansion valve. The analytical approach will obtain the value of MTTF (Mean Time To Failure) system for 250 hours and the availability value is 0,6308 or 63,08% and the unavailability value is 0,3692 or 36,92%.